Food Sovereignty of peasents at Divino, MG: a Geography of Food? - Carneiro, Leonardo de Oliveira (Geografares, 2018)
This article aims to debate about the food sovereignty of peasents at Divino, MG, articulated in the agroecological movement. The methodological approach of this research utilized is the observant participation. Interviews and guided walks in the peasant’s properties are also part of the methodology. The results demonstrate a high level of food sovereignty in this specific group: most of their feeding comes from their lands. This productive diversity is geographically pinpointed in the rural landscape and, above all, it may suggest the possibility of food sovereignty at different scales. Key words: Food Sovereignty, Territory; Agroecology.